Kesesuaian Antara Harapan dan Kenyataan Pasien Umum terhadap Pelayanan Poli Rawat Jalan di RSUD dr. Sayidiman Magetan - Alyaa Syifa Rahmadiani; Putri Asmita Wigati; Eka Yunila Fatmasari (Jurnal Riset Kesehatan Masyarakat, 2025)
Background: RSUD dr. Sayidiman Magetan is a BLUD hospital that benefits from public patients, but public patient visits have decreased in January-July 2024. In addition, the outpatient clinic has the second lowest satisfaction level with a score of 80.43. This condition indicates the need for evaluation to improve general patient satisfaction. The purpose of this study was to analyze the expectations and reality received by general patients towards outpatient poly services from the aspects of tangible, reliability, responsiveness, assurance, and empathy. Methods: This study is a quantitative study with a cross sectional research design, conducted in December 2024-February 2025, and the data analysis used the IPA (Index Performance Analysis) method based on the results of the expected and actual scores. Results: The level of satisfaction with the dimensions of service that are still considered unsatisfactory by respondents is the dimension of reliability and responsiveness, because the level of conformity is still below 86.56%. Meanwhile, the service dimensions that were declared satisfactory were tangible, assurance, and empathy, with a level of conformity above 86.56%. Conclusion: The responsiveness dimension has the lowest level of agreement (83.52%), so patients are less satisfied in this aspect. The reliability dimension was also below average (86.53%), indicating suboptimal satisfaction. In contrast, the dimensions of physical evidence (86.58%), assurance (87.76%), and empathy (88.40%) had above-average levels of conformity, with empathy as the most satisfying aspect for patients.